RESEARCH OF NEUROPHYSIOLOGIC BASES OF GENDER DIFFERENCES IN SPATIAL ORIENTATION (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
The correlated interrelations between the sexual belonging, non-verbal IQ parameters, creativity and efficiency of solving the spatial-shaped task of mazemodel type and the neurophysiologic bases of gender differences in efficiency of spatial orientation were studied. Authentic dominating influence of sex and non-verbal IQ size on efficiency of maze-model task performance is shown. Gender differences of mechanisms of maintenance of the spatial tasks decision are revealed: connected activation of occipital areas and parieta) and frontal areas is found out in men, against tested women to whom activation of only occipital area suffices.
Keywords: non-verbal IQ parameters; gender differences; spatial-shaped task; neurophysiologic; mechanisms of maintenance